Pembuatan jerami terfermentasi probion sebagai pakan alternatif pada ternak sapi terintegrasi di Gampong Blang Krueng Kecamatan Baitussalam Kabupaten Aceh Besar [Making probion fermented straw as an alternative feed in integrated cattle farming in Blang Krueng Village, Baitussalam Sub-District, Aceh Besar District] - Sutriana, Amalia; Hanafiah, Muhammad; Melia, Juli; Aliza, Dwinna (Buletin Pengabdian, 2024)
Farmers, especially those in Blang Krueng Village, Baitussalam Subdistrict, Aceh Besar District, have so far been raising livestock using traditional or semi-extensive patterns, where livestock are released in pastures or rice fields to find their own feed and in the afternoon given grass that has been cut into pieces. The purpose of the activity is to assist farmers in their livestock business, especially in the problem of feed needs that still cannot be met. This activity is carried out using the PRA (Participatory Rural Appraisal) approach. In this case the target audience participates in increasing and analyzing their knowledge about their own conditions so that they can make plans and actions, especially in efforts to raise cattle. The method of processing fermented straw, among others, the straw is aerated so that the moisture content is 40%, the straw is stacked with a length of 2.5 m, a width of 2.5 m and a thickness of 25 cm, on top of the straw layer watered with water that has been mixed with urea until evenly distributed, on top of the straw layer sprinkled with starter until evenly distributed, the straw is stacked again with a thickness of 25 cm trampled until solid, repeated watering of water mixed with urea until evenly distributed, repeated sowing of starter until evenly distributed, so repeated until the pile can reach 3 m, after completion the top is covered with dry leaves such as banana leaves, rice straw is left for at least 3-4 weeks and fermented rice straw is ready to be given to livestock. The results of the service that have been achieved are the availability of alternative feed from fermented straw and can be given to cattle, where the cattle also want to consume it.